The poetic components of the hadith scholars Badr Shaker and Nazik Al-Malaika - jasim kharnoob lazim, Rese.; Naim amouri , Prof. Dr; محمود آبدانان مهدیزاده د.; Abdolhosin taher alrobaei, Prof. Dr (lark, 2024)
The poetic concept first had been appeared in the analysis of the Muslims philosophy for Aristotle book ‘Poetry Art’. Then, this concept had been presented by Hasim Al- Kartaji to indicate the aesthetic function of a discourse. Moreover, Ibn Sina ( 428) was tackled with it as well as. Poetry is an imaginative, consists of lines that equal and rhythmical. In Arabic poetry , it is rhyme. To talk about the poetic principles concerning the poet Nazik Al Malaka and Bader Al Sayaab, the poem is developed in its renewal and modern stage especially in free poetry as far as the new branches that insist its modernist. This fits in poems and their texts concerning the principles that promote the poem as Nazik Al Malaka and Bader Al Sayaab are concerned ( Free poetry). Free poetry is the most important poetic form that forms the modern poetry because of its new ways of making up the poems concerning ; rhythm, content, reality, and dependent in Nazik Al Malaka poetry. The free poetry made revolution concerning the poetic form especially rhythm and rhyme within changing of the foot ‘tafeela’. Bader Al- Sayaab dealt with the types of rhythm ; narration, dialogue, image rhytm as well as the image of thoughts etc.